ANALISIS PENGARUH HUBUNGAN KARYAWAN ( EMPLOYEE RELATION ) TERHADAP KEPUASAN KERJA KARYAWAN PT. MENARA KARTIKA BUANA DI KARANGANYAR - Nur Ahmad; Didik Hermawan (Benefit: Jurnal Manajemen dan Bisnis, 2012)
The purpose of this study is to empirically examine the effect of employee relationsconsisting of employee communication, guidance and discipline affect the job satisfaction of employeesof PT. Kartika Tower Buana in Karanganyar and knowing the relationship among the employeerelations of the most dominant influence on job satisfaction of employees of PT. Kartika Tower Buanain Karanganyar. Based on the results of this research can enrich the study of the phenomenon ofemployee relations and is expected used as a source of information and material for consideration bythe company to increase employee satisfaction. The hypothesis testing in this study using a multiplelinear regression analysis with the t-test, F-test and the coefficient of determination (R2). The populationin this study was all employees of PT. Kartika Tower Buana Karanganyar. While the study samplewas 100 employees of PT. Kartika Tower Buana Karanganyar with accidental sampling as a samplingtechnique. Based on the survey results revealed that communication t-test obtained for 2.845 1.985so that a positive and significant effect on job satisfaction of employees of PT. Kartika Tower BuanaKaranganyar. T-test obtained for guidance is 2.936 1.985 so that a positive and significant effecton job satisfaction of PT. Kartika Tower Buana employee. T-test obtained for discipline is 5.2341.985 so have positive and significant effect on job satisfaction of employees of PT. Kartika TowerBuana Karanganyar. Based on calculations simultaneously T-test obtained is 36.488 2.68 so thatcommunication, guidance and incentives together have a positive and significant effect on jobsatisfaction of employees of PT. Kartika Tower Buana Karanganyar. The coefficient of determination (R2) of 0.533; meant that communication, guidance, discipline can explain the causes of the rising and falling job satisfaction of employees of PT. Kartika Tower Buana Karanganyar by 53.3%, while the remaining 46.7% can be explained by other variables outside the model. The calculations show that discipline is a variable that has a value of beta coefficient greater when compared with the performance, that is equal to 0.415. This suggests that discipline is the most dominant influence on job satisfaction of employees of PT. Kartika Tower Buana Karanganyar compared with guidance and communication.